Role of GmNAC019 transcription factor in salinity and drought tolerance of transgenic Arabidopsis thaliana - Ha Vy, Thai; Cao Nguyen, Nguyen; Lan Xuan, Hoang Thi; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2020)
Increasingly severe drought and salinity stress due to global climate change have made these stresses bigger threats to ecosystem and agriculture. Previous studies reported that GmNAC019, a soybean NAC transcription factor - encoding gene, displayed induced expression upon drought treatment in wild-type cultivars. In this study, drought and salinity stresses were applied on GmNAC019-overexpressing Arabidopsis plants to verify the contribution of GmNAC019 in regulating plant response to the stress conditions. Results from the water loss rate and survival rate assays revealed that the transgenic line conferred improved tolerance to drought stress as evidenced by lower leaf water loss and significantly higher rate of survival than seen in the wild-type plants. Similarly, the survival rate assay for testing salinity effects on plants by growing the plants on MS medium supplemented with different NaCl concentrations also indicated that the transgenic plants had a better tolerance to salt stress as they displayed lower rate of root growth inhibition and higher survival rate. Taken these results altogether, it is suggested that GmNAC019 might play important role in aiding plant response to drought and salinity stresses. Specific functions of this gene should be elaborated in future studies to evaluate its potential application for crop improvement.